UTILIZATION AND EVALUATION OF CRICKET MEAL AS PROTEIN SOURCE IN LAMB RATION - Astuti, Dewi Apri; Khotijah, Lillis; Rismarianty, Andi (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was aimed to evaluate the utilization of cricket (insect) meal as protein source in growing sheep ration. The experiment was conducted using Completely Randomized Design using three treatments with four replicates of local growing sheep (BW 11.24±1.62 kg). The treatments consisted of concentrate containing soybean meal (C), concentrate containing cricket meal with 50% replacement of soybean meal (CM-50) and concentrate containing cricket meal with 100% replacement of soybean meal (CM-100). All the animals were fed 40% forage Brachiaria humidicola and 60% concentrate. The parameters measured were nutrient consumption, rumen fermentation, including methane production, nutrient digestibility and blood metabolites level (glucose, triglyceride and total protein). Result showed that there were no significant differences in dry matter, protein and energy consumptions among three treatments. The digestibility of nutrients and blood metabolites were also similar in all treatments. Concentration of total VFA in control (113 mM.L 1) and CM-50 (116.33 mM.L-1) was significantly lower (P<0.05) than in CM-100 (135 mM.L-1) treatment. Methane estimated from VFA partial in CM-50 (25.22 mmol) was significantly lower than CM-100 (33.93 mmol).